ABU BAKAR BA'ASYIR DAN PERANNYA DALAM MAJELIS MUJAHIDIN INDONESIA (MMI) - afton zuhri adnan; Intan Muthoharoh; Bukhori Abdul Somad; Masruchin Masruchin (Ta'lim, 2023)
ABSTRACTAfter the New Order regime fell, organizations began to emerge, it was shown as a form of freedom in expressing themselves in the Reformation Era. Likewise, the emergence of several Islamic organizations that echo the implementation of Islamic shari'a in Indonesia. These organizations attracted the attention of the general public, including Hizbut Tahrir Indonesia (HTI), the Islamic Defenders Front (FPI), and the Indonesian Mujahidin Council (MMI). They assume that the decline of Muslims is due to the non-implementation of Islamic law. The Indonesian Mujahidin Congress I was the beginning of the birth of the organization named Majelis Mujahidin Indonesia (MMI). Abu Bakar Ba'asyir was one of the people who spearheaded the establishment of MMI. And Abu Bakar Ba'asyir was chosen as Amir Mujahidin. The purpose of this research is to find out whether the thoughts of the MMI organization that contain a lot of controversy in society come from the principle of thought and control of Abu Bakar Ba'asyir or the actions of his followers. the research method used is qualitative research in which it produces descriptive data, this research is a type of library research because the results of the research are more concerned with the search for library data found in reference sources. The end of the author's findings states that Abu bakar Ba'asyir was involved with MMI for approximately 8 years and the rest he resigned.Keywords: Assembly, Mujahidin, Abu Bakar Ba'asyir, Islamic Organization